Seasonal variation of surface seawater radiocarbon in the Andaman Sea as recorded in coral. (December 2022) - Raj, Harsh; Bhushan, Ravi; Banerji, Upasana S.; Jena, Partha Sarathi; Dabhi, Ankur J.
Abstract: Corals provide high-resolution radiocarbon record of the surface ocean. These high-resolution records can provide understanding of the surface ocean conditions and processes regulating these conditions. A Porites coral from the Andaman Sea was investigated for its high-resolution radiocarbon record between 2007 and 2014. The radiocarbon measurement of the coral shows a post-bomb period decline trend (2.7‰ yr −1 ) along with seasonal variations. A positive correlation is observed between the seasonal radiocarbon changes and the stable oxygen isotope values of the coral. The coral registers the seasonal changes in mixed layer depth and sea surface temperature between the monsoon and non-monsoon periods. Recent radiocarbon values of the Andaman Sea surface water have been found to be higher compared to the contemporary atmospheric radiocarbon values. Highlights: Sub-annual variations in coral Δ 14 C record from the Andaman Sea is reported. Seasonal Δ 14 C variations are overlaid on long term declining trend of 2.7‰ yr −1 . Positive correlation between seasonal Δ 14 C changes and δ 18 O changes in the coral. Andaman coral δ 18 O and Δ 14 C values capture the SST and MLD changes respectively.